Future-Proofing Tourism: Artificial Intelligence & Innovation. A Bibliometric Analysis - Polec, Ioana; Torjescu, Ana-Maria; Ciobanu, Emanuel (Proceedings of the ... International Conference on Business Excellence, 2025)
Tourism represents an essential component in nowadays economic, social and cultural environment, a subject that has been tackled by many researchers. Due to the changing environment, the tourism industry is impacted by many changes and aspects including artificial intelligence and innovation. These two key elements are transforming tourism by enhancing personalized experiences, optimizing travel planning, and creating smarter, more sustainable destinations for the future. Even though there has been a lot of focus on this topic, the relationship between these was not deeply investigated. This article aims to address the gap by determining a starting point of the linkage between tourism, artificial intelligence and innovation and their future together. Through analyzing existing literature and applying a bibliometric analysis, the study examines 256 specific scientific papers from the Scopus database on this topic. The metadata is examined through VOSviewer software by creating co-occurrence and co-citations of journals, authors, articles and keywords. The outcome of data shows a significant increase in the scientific literature. The methodological framework has four stages related to the collection of data, examination of data, representation of data and interpretation of data. The findings acknowledge the topic’s complexity by presenting a thorough analysis of the scientific framework, delivering valuable insights for stakeholders, and emphasizing crucial directions for future research that require further exploration.